Methods for Distance Determination Between Objects on Video Recordings Using Geographic Information Systems - A. G. Boyarov; O. O. Vlasov; A. A. Godlevskii; S. B. Shavykina (Теория и практика судебной экспертизы)
The article summarizes the research experience gained by forensic expert institutions of the Russian Ministry of Justice under assessment of the distance determination accuracy using orthophotomaps of GIS “Yandex Maps” and GIS “Google Earth”. On the basis of this assessment the methodological approach is proposed to solve the expert task of determining distances on video records using various geographic information systems (hereinafter GIS), including cases of establishing circumstances of road accidents (hereinafter accidents). As part of this approach, methods for GIS data verification are described.